Calcium intake and health - Cormick, Gabriela (2019)
There are striking inequities in calcium intake between rich and poor populations. Appropriate calcium intake has shown many health benefits, such as reduction of hypertensive disorders of pregnancy, lower blood pressure particularly among young people, prevention of osteoporosis and colorectal adenomas, lower cholesterol values, and lower blood pressure in the progeny of mothers taking sufficient calcium during pregnancy. Studies have refuted some calcium supplementation side effects like damage to the iron status, formation of renal stones and myocardial infarction in older people. Attention should be given to bone resorption in post-partum women after calcium supplementation withdrawal. Mechanisms linking low calcium intake and blood pressure are mediated by parathyroid hormone raise that increases intracellular calcium in vascular smooth muscle cells leading to vasoconstriction. At the population level, an increase of around 400-500 mg/day could reduce the differences in calcium intake between high- and middle-low-income countries. The fortification of food and water seems a possible strategy to reach this goal.